2020
DOI: 10.3390/microorganisms8121979
|View full text |Cite
|
Sign up to set email alerts
|

Greater Biofilm Formation and Increased Biodegradation of Polyethylene Film by a Microbial Consortium of Arthrobacter sp. and Streptomyces sp.

Abstract: The widespread use of polyethylene (PE) mulch films has led to a significant accumulation of plastic waste in agricultural soils. The biodegradation of plastic waste by microorganisms promises to provide a cost-effective and environmentally-friendly alternative for mitigating soil plastic pollution. A large number of microorganisms capable of degrading PE have been reported, but degradation may be further enhanced by the cooperative activity of multiple microbial species. Here, two novel strains of Arthrobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…Further, Streptomyces may be critically involved in plastics’ degradation. Recently, Han et al ( 2020 ) found that a Streptomyces strain, isolated from agricultural soils, was able to grow with mulching film as carbon source and to thereby degrade the mulching film over time Therefore, we posit that Streptomyces is to some extent associated with PBAT’s degradation in the DPBOS treatment soil.…”
Section: Discussionmentioning
confidence: 86%
“…Further, Streptomyces may be critically involved in plastics’ degradation. Recently, Han et al ( 2020 ) found that a Streptomyces strain, isolated from agricultural soils, was able to grow with mulching film as carbon source and to thereby degrade the mulching film over time Therefore, we posit that Streptomyces is to some extent associated with PBAT’s degradation in the DPBOS treatment soil.…”
Section: Discussionmentioning
confidence: 86%
“…Consequently, the biofilm formation alters the polymer properties such as changes in functional groups, hydrophobicity/hydrophilicity, surface morphology, molecular weight, and crystallinity. Biofilm initiation enhances the carbon source utilization from immiscible substrates (Han et al, 2020). A recent study provided insights into the basis of biofilm formation on plastics (i.e., PLA, PET) surfaces and the role of conditioning films.…”
Section: Biofilms Forming Properties Of Microbesmentioning
confidence: 99%
“…It is therefore plausible that pristine microplastics practically do not exist in the aquatic environment. In addition, the biofilm on microplastics has been shown to harbor microorganisms capable of degrading plastics at a rather high abundance (McCormick et al, 2014), potentially contributing to their degradation in the environment (Han et al, 2020).…”
Section: Particle-associated Biofilmmentioning
confidence: 99%